INTEGRATED APPLICATION OF TGI AND NDMI FOR IDENTIFYING CHEMICAL DEFORESTATION IN THE PANTANAL, BRAZIL - Ferreira, Jean Carlos; Dias, André Pereira; Gambati, Joberth Firmino (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
This study presents an innovative approach for detecting and monitoring chemical deforestation in the Brazilian Pantanal, revealing alarming impacts of aerial herbicide spraying on native vegetation. Through the integration of the Triangular Greenness Index (TGI) and Normalized Difference Moisture (NDMI) spectral indices applied to Sentinel-2A images, we identified characteristic patterns of chemical degradation in 158,776 hectares of wetlands and native vegetation formations in the Pantanal of Barão de Melgaço, Mato Grosso, that occurred between 2021 and 2023. The developed methodology demonstrated high precision (89% accuracy) in discriminating between pesticide damage and other natural or anthropogenic disturbances, revealing specific spectral signatures and spatial patterns typical of aerial application. The results provided crucial scientific evidence that supported environmental inspection actions, culminating in the embargo of the affected areas and the application of fines and environmental recovery commitments. In addition to demonstrating the effectiveness of TGI-NDMI integration for environmental monitoring, the study warns of a new frontier of degradation in tropical humid ecosystems, highlighting the urgency of specific public policies to regulate aerial spraying and protect these sensitive ecosystems. The approach developed presents itself as a strategic tool for environmental monitoring, allowing for the rapid detection and accurate assessment of large-scale damage, with potential application in other tropical biomes threatened by similar chemical deforestation practices.